Carlo Fantappiè, Ecclesiologia e Canonistica Venezia: Marcianum Press, 2015, 439 pp. - Gałkowski, Tomasz (Philosophy and Canon Law, 2021)
Carlo Fantappiè, Ecclesiologia e Canonistica Venezia: Marcianum Press, 2015, 439 pp.